2014
DOI: 10.1371/journal.pone.0103401
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya MicroRNAs Are Responsive to Papaya meleira virus Infection

Abstract: MicroRNAs are implicated in the response to biotic stresses. Papaya meleira virus (PMeV) is the causal agent of sticky disease, a commercially important pathology in papaya for which there are currently no resistant varieties. PMeV has a number of unusual features, such as residence in the laticifers of infected plants, and the response of the papaya to PMeV infection is not well understood. The protein levels of 20S proteasome subunits increase during PMeV infection, suggesting that proteolysis could be an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…MicroRNA coding genes predicted to target proteasome-related proteins, for instance ubiquitin-3-ligases, also accumulated in C. papaya sticky-diseased leaves suggesting their involvement in the control of protein turnover [7]. However, limited knowledge about key players of the PMeV x C. papaya interaction mechanism impairs the development of virus resistant plant genotype(s) and a differential proteomic study investigating the effects of infection at the protein level could be of value to this effort.…”
Section: Papaya Meleira Virus (Pmev) Infects Papaya (Carica Papaya Lmentioning
confidence: 99%
“…MicroRNA coding genes predicted to target proteasome-related proteins, for instance ubiquitin-3-ligases, also accumulated in C. papaya sticky-diseased leaves suggesting their involvement in the control of protein turnover [7]. However, limited knowledge about key players of the PMeV x C. papaya interaction mechanism impairs the development of virus resistant plant genotype(s) and a differential proteomic study investigating the effects of infection at the protein level could be of value to this effort.…”
Section: Papaya Meleira Virus (Pmev) Infects Papaya (Carica Papaya Lmentioning
confidence: 99%
“…However, the conservation of mature miRNAs between plant species has enabled a computer-based approach to predict the secondary structures of the sequences surrounding miRNA. Actually, 4,251 plant mature miRNA sequences from the Plant miRNAs Database were used to search for hairpin structures in the C. papaya genome [ 60 ]. 462 known miRNA sequences were detected in 537 hairpins in the C. papaya genome; additionally, these miRNAs were classified into 72 miRNAs families [ 60 ].…”
Section: Papaya and Pmev Interactionmentioning
confidence: 99%
“…Changes in miRNA expression are associated with viral infection in Arabidopsis [ 61 ], and viral protein-induced alterations in miRNA expression have been associated with symptom development in Nicotiana tabacum [ 62 ]. Therefore, in order to understand the unique plant-virus interaction between PMeV and C. papaya , and, consequently, the mechanisms involved in the onset of sticky disease symptoms, the miRNA response of the plant to infection was investigated [ 60 ]. The MicroRNAs that target the components of the 20S and 26S proteasomal degradation processes and components of other stress response pathways were studied.…”
Section: Papaya and Pmev Interactionmentioning
confidence: 99%
“…Viruses are economically important plant pathogens that typically cause symptoms of yellowing, mosaic, twisting and even necrosis of leaves, and plant death in many cases. Studies with many different viruses have shown that virus‐infected plants generally have a changed expression profile of miRNAs (Abreu et al ., ; Amin et al ., ; Bazzini et al ., ; Chen et al ., , ; Cillo et al ., ; Du et al ., ; Feng et al ., , ; Guo et al ., ; Lang et al ., , ; Liu et al ., ; Naqvi et al ., ; Pradhan et al ., ; Sun et al ., ; Wang et al ., ; Xu et al ., ; Yang et al ., ) and, in some cases, these changes are associated with viral symptoms (Gao et al ., ; Lian et al ., ; Romanel et al ., ). Bazzini et al.…”
Section: Introductionmentioning
confidence: 99%